PENGARUH INSEKTISIDA ORGANOKLORIN DIKOFOL TERHADAP DAYA TETAS TELUR IKAN LELE (Clarias gariepinus L.) - Mawarni, Mawarni; Sumarmin, Ramadhan; Kasmeri, S.Si, M.Si., Ria (Pendidikan Biologi, 2014)
ABSTRACT  As the development of catfish cultivating in needs to be supported by the provision of sufficient seed  in  term  of  quality  and  quantity. Therefore,  it  is  necessary  to  improve  techniques  of  catfish hatchery. In the seeding technique, cultivators should consider these factors in the hatching process including water quality. This research aims to know the influence of dikofol organochlorine insecticides against the hatching rate of eggs, normal and abnormal larvae in catfish. This research was conducted in November 2013 at the Zoology Laboratory of biology Department, Faculty of Mathematics and Natural Scince Padang State University. This research is experimental research, used Completely Randomized Design (CRD), 4 treatments and 6 replications. With A treatment   (control), B treatment (0.001%), C treatment (0.002%), and D treatment (0.003%). Observations were made on eggs that hatched into larvae after 2 days incubation. The data in research on hatching rate of eggs, normal and abnormal larvae in catfish were analyzed by ANOVA, and continued by LSD. The results show that hatching rate of egg in A treatment (91.67%), B (81.67%), C (77.50%) and D (74.17%). In normal larvae obtained the highest results on A treatment (99.00%), while the lowest in D treatment (96.00%), for abnormal larvae obtained the highest results in D treatment (3.66%), while the lowest in A treatment (0.93%). It can be concluded that dikofol organochlorine insecticides decreased the  hatching rate of egg and  normal larvae, and increased an abnormal larvae in catfish.